Genes underlying cold acclimation in the tea plant (Camellia sinensis (L.) Kuntze) - L. S. Samarina; L. S. Malyukova; M. V. Gvasaliya; A. M. Efremov; V. I. Malyarovskaya; S. V. Loshkareva; M. T. Tuov (Вавиловский журнал генетики и селекции)
The article reviews the latest studies showing the diversity of genetic mechanisms and gene families underlying the increased cold and frost tolerance of tea and other plant species. It has been shown that cell responses to chilling (0…+15°C) and freezing (< 0°C) are not the same and gene expression under cold stress is genotype-specific. In recent decades, progress has been made in understanding the genetic mechanisms underlying the cold response of plants – ICE1 (inducer of CBF expression 1), CBF (C-repeat-binding factor), COR (cold-regulated genes) pathways and signaling have been discovered. The ICE, CBF and DHN gene groups play a key role in the cold acclimation of the tea plant. The accumulation of CBF transcripts occurs after 15 min of chilling induction, and longer cold stress leads to accumulation of CBF transcripts. It is shown that the transcripts of the CsDHN1, CsDHN2 and CsDHN3 genes accumulate at a higher level in resistant genotypes of tea in comparison with susceptible cultivars during freezing. CBF-independent pathways include genes involved in metabolism and transcription factors such as HSFC1, ZAT12, CZF1, PLD (phospholipase D), WRKY, HD-Zip, CsLEA, LOX, NAC, HSP, which are widely distributed in plants and are involved in the basic mechanisms of tea resistance to cold and frost. The most recent studies show an important role of miRNA in the mechanisms of response to chilling and freezing in tea. The data obtained on different plant species may correlate with the mechanisms of frost tolerance of tea and are the basis for future studies of the signaling pathways of response to cold in the tea plant. The results of the research emphasize the need to further explore the ways in which various genes regulate the tolerance of tea to cold stress to find the molecular markers of frost tolerance.